2019
DOI: 10.1001/jamanetworkopen.2019.16777
|View full text |Cite
|
Sign up to set email alerts
|

Association of Periconception Paternal Body Mass Index With Persistent Changes in DNA Methylation of Offspring in Childhood

Abstract: IMPORTANCE While prenatal nutrition and maternal obesity are recognized as important contributors to epigenetic changes and childhood obesity, the role of paternal obesity in the epigenome of offspring has not been well studied. OBJECTIVES To test whether periconception paternal body mass index (BMI) is associated with DNA methylation patterns in newborns, to examine associations between maternal and paternal BMI and the epigenome of offspring, and to examine persistence of epigenetic marks at ages 3 and 7 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
2
36
1
Order By: Relevance
“…This analysis found that methylation at one CpG site, cg19357369 (chr4:2429884), was significantly increased in obese men in sperm and blood (2% higher DNA methylation, P = 8.95 × 10 −8 , Fig 6D ). Finally, we compared our results with those of a previous study, which identified associations between paternal weight and offspring DNA methylation in a sample of 429 father-mother-child triads [ 29 ]. Out of the nine probes at which Noor and colleagues found an association between cord blood DNA methylation and paternal periconceptional BMI, only one showed a nominally significant association in consistent effect direction in the sperm obesity EWAS ( P = 0.028, DNA methylation difference = 6%) and the combined mixed effects model in blood and sperm ( P = 0.01, DNA methylation difference = 4%).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis found that methylation at one CpG site, cg19357369 (chr4:2429884), was significantly increased in obese men in sperm and blood (2% higher DNA methylation, P = 8.95 × 10 −8 , Fig 6D ). Finally, we compared our results with those of a previous study, which identified associations between paternal weight and offspring DNA methylation in a sample of 429 father-mother-child triads [ 29 ]. Out of the nine probes at which Noor and colleagues found an association between cord blood DNA methylation and paternal periconceptional BMI, only one showed a nominally significant association in consistent effect direction in the sperm obesity EWAS ( P = 0.028, DNA methylation difference = 6%) and the combined mixed effects model in blood and sperm ( P = 0.01, DNA methylation difference = 4%).…”
Section: Resultsmentioning
confidence: 99%
“…In Project Viva (a cohort that also contributed results to our meta-analysis), Noor et al identified nine CpGs where cord blood methylation was associated with periconceptional paternal BMI after adjustment for maternal BMI (20). In our results at birth, we found the same direction of estimated effect at 7/9 CpGs.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, a recent systematic review (13) found conflicting evidence on the association between paternal body mass index (BMI) and offspring birthweight, and some evidence of an association with greater offspring BMI, weight or body fat mass in childhood. A small number of studies have also found links between paternal BMI and sperm or offspring neonatal blood DNA methylation, but these have been based on candidate genes and/or had very limited sample sizes (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A strong association between maternal obesity before pregnancy and childhood obesity is reported to be due to a combination of different in utero programming mechanisms [4,6,25]. Paternal obesity might play an additional role through epigenetic alterations, but this needs further confirmation [26]. Since there is also a correlation between current parental obesity and childhood obesity, the actual food and family environment interfere as well [1,3].…”
Section: Discussionmentioning
confidence: 99%